An artificial molecular switch that mimics the visual pigment and completes its photocycle in picoseconds - Sinicropi, Adalgisa; Martin, Elena; Ryazantsev, Mikhail; Helbing, Jan; Briand, Julien; Sharma, Divya; Léonard, Jérémie; Haacke, Stefan; Cannizzo, Andrea; Chergui, Majed; Zanirato, Vinicio; Fusi, Stefania; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
Single molecules that act as light-energy transducers (e.g., converting the energy of a photon into atomic-level mechanical motion) are examples of minimal molecular devices. Here, we focus on a molecular switch designed by merging a conformationally locked diarylidene skeleton with a retinal-like Schiff base and capable of mimicking, in solution, different aspects of the transduction of the visual pigment Rhodopsin. Complementary ab initio multiconfigurational quantum chemistry-based computations and time-resolved spectroscopy are used to follow the light-induced isomerization of the switch in methanol. The results show that, similar to rhodopsin, the isomerization occurs on a 0.3-ps time scale and is followed by <10-ps cooling and solvation. The entire (2-photon-powered) switch cycle was traced by following the evolution of its infrared spectrum. These measurements indicate that a full cycle can be completed within 20 ps.